1985
DOI: 10.1080/01635588509513860
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of dietary fat and antiestrogen treatment on DMBA‐induced mammary tumors in the rat

Abstract: This study was designed to determine whether an estrogenic mechanism is involved in dietary fat-modulated tumor development and growth. Female Sprague-Dawley rats were placed on a semipurified low-fat (2% fat), high-saturated fat (20% fat), or high-polyunsaturated fat (20% fat) diet at 21 days of age. A single dose of 7,12-dimethylbenz[a]anthracene (DMBA, 10 mg) was administered intragastrically at 50 days of age. Two studies were performed. One tested the effectiveness of antiestrogen treatment (either tamoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Early antiestrogenic studies of (1) and its trans isomer have shown that: (i) compound (1) is a weaker antiestrogen than tamoxifen but is devoid of intrinsic agonist activity (Magarian & Benjamin, 1975;Pento et al, 1981); (ii) compound (1) and tamoxifen were equally effective in reducing the growth of established 7,12-dimethylbenz[a]-anthracene (DMBA)-induced rat mammary tumors, but (1) induced greater reduction in the occurrence of new tumors (Pento, Magarian & King, 1982;King, Pento, Magarian & Brueggemann, 1985;King, Magarian, Terao & Brueggemann, 1985); (iii) the trans isomer of (1) is devoid of any biological action (Pento et al, 1981).…”
Section: Structure-activity Relationmentioning
confidence: 99%
“…Early antiestrogenic studies of (1) and its trans isomer have shown that: (i) compound (1) is a weaker antiestrogen than tamoxifen but is devoid of intrinsic agonist activity (Magarian & Benjamin, 1975;Pento et al, 1981); (ii) compound (1) and tamoxifen were equally effective in reducing the growth of established 7,12-dimethylbenz[a]-anthracene (DMBA)-induced rat mammary tumors, but (1) induced greater reduction in the occurrence of new tumors (Pento, Magarian & King, 1982;King, Pento, Magarian & Brueggemann, 1985;King, Magarian, Terao & Brueggemann, 1985); (iii) the trans isomer of (1) is devoid of any biological action (Pento et al, 1981).…”
Section: Structure-activity Relationmentioning
confidence: 99%
“…Reports from our laboratory (15,16) and others (20,23) have demonstrated that the introduction of a dichlorocyclopropyl or dihydroclopropyl moiety in place of the olefinic bridge in estrogenic stilbenes greatly reduces or abolishes their estrogenic action. One compound, analog II (Chart 1), has antiestrogenic properties without estrogen agonist activity in the mouse and is comparable in activity to tamoxifen against the hormone-dependent 7,12-dimethyl benz[a]anthracene-induced rat mammary tumor model (24,25). Structure-activity relationship studies of some of the analog II derivatives (15)(16)(17)26) led us to design more effective cyclopropyl antiestrogens.…”
Section: Introductionmentioning
confidence: 99%